"Am I Becoming a Serial Killer?" A Case Study of Cognitive Behavioral Therapy for Mental Illness Anxiety. Issue 3 (21st August 2015) - Gelinas, Bethany L.; Hadjistavropoulos, Heather
Abstract : Background: Although mental illness anxiety is described in the literature, there is very little information on which to draw when treating individuals who present with fears and worries about mental health. In fact, we identified no previous case descriptions focused on this form of anxiety and treated from a cognitive behavioral perspective.Aims: The current case study aims to advance the understanding of the clinical picture of mental illness anxiety, and facilitate the understanding of how cognitive behavioral techniques for health anxiety can be effectively adapted and implemented for such a case.Method: A case study approach was adopted in which a baseline condition and repeated assessments were conducted during an 8-week treatment and 2-month follow-up period. In the current case study, we discuss the assessment, conceptualization, and cognitive behavioral treatment of a 24-year old woman who presented with mental illness anxiety. Several common health anxiety assessment tools and cognitive behavioural techniques were adapted for her particular clinical presentation.Results: Consistent with research evidence for health anxiety, significant improvements in health anxiety and anxiety sensitivity were seen after eight sessions of therapy and maintained at 2-month follow-up.Conclusions: The results provide preliminary evidence that cognitive behavioral techniques for health anxiety can be effectively and efficiently adapted for mental illness anxiety. However, the lack of available research pertaining to mental illness anxiety contributes to challenges in conceptualization, assessment and treatment.